Spatial and temporal distribution characteristics and prediction analysis of nitrogen and phosphorus surface source pollution in Shandong Province under the climate and land use changes - Li, Qingsong; Zhang, Jincai; Zhang, Jiawen; Gao, Huishan; Chen, Weiqiang; Huang, Junchang; Guo, Yulong; Yue, Shuaijun; Li, Genming (Frontiers in Ecology and Evolution, 2023)
The aim of this study was to explore the characteristics of non-point source pollution of nitrogen (N) and phosphorus (P) under the background of climate and land use in Shandong Province. First, using the InVEST NDR module in the model, N and P non-point source pollution in 2010 and 2020 in Shandong Province were simulated; then, based on precipitation data under three different global climate models (MRI-ESM-0, GFDL-ESM4, and Ec-Earth3) and two Shared Socioeconomic Pathways (SSP245 and SSP585), land use data under two Shared Socioeconomic Pathways (SSP245 and SSP585) were used to simulate and predict the non-point source pollution of N and P in Shandong Province in 2030. The results showed the following: (1) On the time scale, the output load and total output of N and P decreased during 2010–2020, while the output load and total output of N and P increased during 2020–2030. (2) On the spatial scale, the spatial distribution of N and P output loads in 2010, 2020, and 2030 is roughly the same, being “low in the northwest and high in the southeast”. (3) Different climate scenarios have a great influence on N and P output load and total output, and the N and P pollution in the SSP585 scenario is more serious. The total output of N and P did not change much in different climate models, while the spatial distribution of the output load of N and P varied significantly, indicating that different climate models had a greater impact on the spatial distribution of the output load of N and P. (4) The overall cold hot spot pattern of nitrogen and phosphorus pollution in Shandong Province is stable, basically showing a “band + cluster + scatter” distribution pattern; the hot spot area in the central and southern region of Shandong Province changes little regardless of the model, the northwest is basically a cold spot area, and the nitrogen and phosphorus hot spot area under the SSP245 scenario in Ec-Earth3 model had the least amount of change. According to research results, combined with the actual situation of Shandong Province, it is hoped that it can provide theoretical basis for the prevention and control of non-point source pollution in Shandong Province in the future.